2020
DOI: 10.1080/10548408.2020.1835787
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic pricing assuming demand shifting: the alpine skiing industry

Abstract: Changes in a company's pricing strategy have the potential to influence profitability. Data from choice-based conjoint questionnaire were used to estimate revenue-maximizing dynamic prices accounting for both demand shifting and market expansion. The results show that dynamic prices induce greater demand and could increase revenue by 0.5% to 7.5%. Moreover, skiers have a strong preference and higher willingness-to-pay for good weather-related skiing conditions, suggesting that skiers prefer skiing during the m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 60 publications
0
11
0
Order By: Relevance
“…Dynamic pricing refers to a pricing approach in which the price of a product or service changes depending on a variety of criteria. (Malasevska et al, 2020). The strategy for changing and designing dynamic prices for goods and services in tourism village activities needs to be mastered by tourism village actors so that it is easy for third parties such as OTAs to participate in selling the products.…”
Section: Resultsmentioning
confidence: 99%
“…Dynamic pricing refers to a pricing approach in which the price of a product or service changes depending on a variety of criteria. (Malasevska et al, 2020). The strategy for changing and designing dynamic prices for goods and services in tourism village activities needs to be mastered by tourism village actors so that it is easy for third parties such as OTAs to participate in selling the products.…”
Section: Resultsmentioning
confidence: 99%
“…The obtained results suggested that most skiers will ski on sufficient occasions to receive at least a 50% discount on the daily season ticket price. Another study analyzed how changes in a company's pricing strategy can influence its profitability [75]. This research showed that dynamic pricing induces higher demand and thus can increase revenues.…”
Section: Discussionmentioning
confidence: 99%
“…Despite such negative consequences, many service firms are shifting from simpler differential pricing to more complex algorithms that combine multiple criteria. For example, many ski resorts are moving away from seasonal passes and student discounts in favor of algorithms that include weather conditions, day of the week, and demand (Malasevska et al 2020). Dynamic pricing's spread to new service contexts and the ensuing firestorms underscore the need for service providers to better understand the negative consequences of this pricing tactic.…”
Section: Introductionmentioning
confidence: 99%